ANALISIS PERSPEKTIF IDEALISME DAN REALISME TERHADAP KURIKULUM MERDEKA PENDEKATAN DEEPLEARNING BAHASA INDONESIA - Rizky Fitriyanti Pradani; Waode Dewi Handayani; Teguh Setiawan; Siti Rohmatul Ummah; Nensy Megawati Simanjuntak (Aksara, 2025)
This study aimed to examine the implementation of the Independent Curriculum in Indonesian language learning through the philosophical perspectives of idealism and realism, and to explore how these perspectives are integrated with the deep learning approach. This study employed a qualitative research method involving document analysis and semi-structured interviews conducted with three Indonesian language teachers who had at least two years of experience in implementing the Merdeka Curriculum, as well as one language education lecturer with an academic background in educational philosophy. Content analysis was employed to interpret the philosophical meanings that emerged during the implementation of the curriculum. The results show that the idealist perspective emphasizes the cultivation of students’ moral, spiritual, and character values through Indonesian language learning. In contrast, the realist perspective highlights real-life experiences, practical skills, and the relevance of learning to everyday life. The deep learning approach serves as a bridge between the two philosophies by integrating reflective discussions on moral values with project-based, contextual Indonesian language learning activities identified in classroom practices. Therefore, the Independent Curriculum is not only regarded as an educational innovation but also as a transformation of the educational paradigm that holistically integrates idealism and realism. The findings of this study contribute to the development of more meaningful, adaptive, and contextually relevant Indonesian language learning strategies in the modern educational era.